Buying into Change : Mass Consumption, Dictatorship, and Democratization in Franco's Spain, 1939-1982 - Gómez del Moral, Alejandro J. (Book collections on Project MUSE., 2021)
"Buying into Change examines how the development of a mass consumer society under the dictatorship of Generalissimo Francisco Franco (1939-1975) inserted Spain into transnational consumer networks and set the stage for Spain's transition to democracy during the late 1970s"--